PENERAPAN MEDIA PEMBELAJARAN “PUZZLE PECAHAN” UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS II PADA PEMBELAJARAN MATEMATIKA DI SDN 01 MOJOREJO KOTA MADIUN - Syal Sabilla Pratiwi; Candra Dewi; Nur Hayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research uses observations in class II SDN 01 Mojorejo Kota Madiun. The results of observations made show that there is a lack of students' understanding of Mathematics learning. The problem that occurs in Mathematics learning is lack of student motivation in fraction material. This type of research uses Classroom Action Research (PTK). There are four main activities in this research, namely planning, implementation, observation and reflection. The subject of this research involved 28 class II students. data collection techniques using observation techniques and test questions in Cycle I and Cycle II. The results of this research show that interactive multimedia as a learning medium in Mathematics, fraction material, can increase students' learning motivation. It can be seen that the results of the test questions in Cycle I with an average score of 57.51% and Cycle II with an average score of 80.46%. From the results of the comparison of increasing changes between Cycle I and Cycle II, it can be concluded that the learning media "Fraction Puzzle "This can increase learning motivation.